Click Car Services / Kilorina Ranis … [et al.] - Ranis, Kilorina; Paukin, Clementina; Salihin, Shaziela Shazrieana; Pundus, Erninttey Sirah; Mohd Zaidi, Nur Murniza (Faculty of Computer and Mathematical Sciences, 2022)
Click Car Services is a mobile application that provides car rental services targeting people who live in the city and tourist attraction areas in East Malaysia. The application will help the tourists and locals by having a proper and efficient mobile application to rent cars instantly. Existing car rental services do not offer a secure and safer system for managing the user's personal information and data, which can lead to an issue of fraud or identity theft. Furthermore, with the digitalization evolution, the application may help to provide a quick response in terms of documentation, deal, and agreement. Users can get an instant car rental in real-time based on the location and time by using the application. This function can enhance the user's experience without going through many procedures and hustles when renting a car. The method used for this project is the three Waterfall methods which consist of analysis, requirement specification, and design. In a nutshell, this application provides many help to the users by offering easy access to car rental through mobile devices, enhancing users' experience, easy access to local attractions, and upgrading the transportation rental system in East Malaysia.